2021
DOI: 10.1002/glia.24013
|View full text |Cite|
|
Sign up to set email alerts
|

p70S6K on astrocytes protects dopamine neurons from 1‐methyl‐4‐phenylpyridinium neurotoxicity

Abstract: Our recent finding has demonstrated that astrocytes confer neuroprotection by endogenously producing ciliary neurotrophic factor (CNTF) via transient receptor potential vanilloid 1 (TRPV1) in Parkinson's disease (PD). In this study, the possible molecular target for TRPV1‐mediated CNTF production and its neuroprotective effects on dopamine neurons were further investigated. For comparison, glial cell‐line derived neurotrophic factor (GDNF) was also examined. The results show that TRPV1‐ribosomal protein 70 S6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Furthermore, we found that only stimulated animals exhibited increased p70s6k expression. Given that increased p70s6k expression in astrocytes protects 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-inoculated cultured neurons [ 63 ], it is reasonable to assume that subthalamic stimulation may modulate astrocytes preferentially to an alternative and neuroprotective phenotype than to a neurotoxic phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found that only stimulated animals exhibited increased p70s6k expression. Given that increased p70s6k expression in astrocytes protects 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-inoculated cultured neurons [ 63 ], it is reasonable to assume that subthalamic stimulation may modulate astrocytes preferentially to an alternative and neuroprotective phenotype than to a neurotoxic phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Astrocyte is known to be involved in neuronal survival by expressing neurotrophic factors (NTFs) [ 5 , 30 , 31 ]. Accordingly, we hypothesized that astrocytes rescued by treatment with IL-13NA ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, CBD, by activating the astrocytic transient receptor potential vanilloid 1 (TRPV1) [19], enhanced the endogenous neuroprotective response of ciliary neurotrophic factor (CNTF). Specifically, activation of TRPV1 on astrocytes increases endogenous CNTF synthesis in vivo, enhancing the viability of dopaminergic neurons through activation of the CNTF receptor alpha subunit (CNTFRα) and preventing neurodegeneration and inducing the recovery of motor performance after administration of MPP + and 6-OHDA in PD rat models [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%